The Practical Challenges of Diagnosis and Treatment Options in Persistent Pulmonary Hypertension of the Newborn: A Developing Country's Perspective - Nakwan, Narongsak (American Journal of Perinatology, 2018)
Persistent pulmonary hypertension of the newborn (PPHN) is a complication of several respiratory diseases characterized by an elevation in pulmonary vascular resistance with resultant right-to-left shunting of blood and severe hypoxemia in the neonatal period. PPHN carries a high rate of morbidity and mortality, particularly in limited-resource settings (low-income and/or developing country). Echocardiography remains the gold standard for diagnosis of PPHN. Modern therapies such as inhaled nitric oxide, high-frequency oscillatory ventilation, extracorporeal membrane oxygenation, and/or other pulmonary vasodilators agents can reduce the mortality rate of PPHN. Unfortunately, echocardiography and the use of these modern therapies are often difficult for a medical institution to provide for patients in developing countries, even when a timely diagnosis of PPHN has been made. In this review, the practical challenges of timely diagnosis of PPHN and efficient use of available treatment options faced by pediatricians or neonatologists in limited-resource settings are discussed.
Keywords: persistent pulmonary hypertension of the newborn; developing country; diagnosis; management; newborn